A joint limit theorem for periodic Hurwitz zeta-functions with algebraic irrational parameters - Genienė, Danutė; Rimkevičienė, Audronė (Mathematical Modelling and Analysis, 2013)
In the paper, a joint limit theorem for weakly convergent probability measures in ℂ r for periodic Hurwitz zeta-functions with algebraic irrational parameters satisfying certain independence conditions is obtained.